The method of searching for the ratio of design and operating factors in relation to low-speed compressor stages - S. S. Busarov; A. V. Nedovenchany; T. A. Vinnikova; N. G. Sinitsin; K. A. Bakulin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper presents a methodology for finding the ratio of design and operating factors in relation to lowspeed compressor stages. The technique is based on the simplex method, which allows you to choose from a database created on the basis of a well-known technique for calculating the working processes of low-speed compressor stages, the best solution for specific search criteria taking into account their importance. The technique is implemented in Microsoft Excel, an example of the implementation of the technique with five criteria is presented: temperature, flow rate, indicator efficiency, weight and overall dimensions.